Characteristics of Investment Activity of Commercial Banks - Mannopova Shaxnoza Elshodovna; Raimberdiyev Samandar Sherzod ogli (Research Parks Publishers, 2022)
Limiting the accumulation of capital and supporting competition in the money market is achieved by the Central Bank's control over the activities of commercial banks. Therefore, Central Bank manages the money supply through their assets (primarily loan operations) by influencing the dynamics of deposits of these banks. In addition, commercial banks are the main source of lending to the economy. The Central Bank instructs commercial banks to distribute loans and direct them to important material and social sectors of the economy. The central bank is made up of funds belonging to the Government, in regulating the money supply from the budgetuses. Due to the difference between the time of receipt of state budget revenues and the time of financing budget expenditures, a certain amount of money is accumulated. The central bank will use these funds temporarily. Typically, government-owned funds are kept on the Central Bank’s balance sheet. Therefore, the Central Bank will be able to manage these funds.